Metric for three-dimensional alignment of molecules - Makhija, Varun; Ren, Xiaoming; Kumarappan, Vinod (My University, 2012)
In an effort to clarify the three-dimensional alignment dynamics of polyatomic molecules, we propose a single measure for the degree of angular confinement of such molecules. The measure proposed for three-dimensional orientation is the angle of the single rotation that takes the molecule to the desired target orientation. Further, taking into account the D2 symmetry of a three-dimensionally aligned distribution, a symmetrized version of the measure is constructed that serves as a direct indicator of the degree of three-dimensional alignment of a distribution. The calculation of the rotational dynamics of iodobenzene under the influence of two cross-polarized laser pulses demonstrates the effectiveness of the proposed metric.